La Summa Alexandrinorum : Abrégé arabo-latin de l'Éthique à Nicomaque d'Aristote. Édition critique, traduction française et introduction - Woerther, Frédérique, (Islamic Philosophy, Theology and Science. Texts and Studies ;, 2020)
This volume contains the first critical edition of the Summa Alexandrinorum , that is the medieval Latin translation made in 1243 by Hermann the German of an Arabic abridgment of the Nicomachean Ethics known as the Iḫtiṣār al-Iskandarānīyīn . It is accompanied by a French translation. The volume also contains a full study of the manuscript tradition of the Latin text and sets out the principles used in the edition, which takes account, where necessary, of the Arabic version of the text, which has survived in the form of fragments. A study of the origin of the Summa Alexandrinorum and the relations between the Summa and the fragments and testimonies which are extant in other traditions and different languages completes the volume. Ce volume propose la toute première édition critique, accompagnée d'une traduction française, de la Summa Alexandrinorum , traduction latine médiévale exécutée en 1243 par Hermann l'Allemand d'un abrégé arabe de l' Éthique à Nicomaque connu sous le titre d' Iḫtiṣār al-Iskandarānīyīn . Il présente également une étude complète de la tradition manuscrite du texte latin, et les principes d'édition adoptés dans l'édition, qui prennent en compte, ponctuellement, la version arabe du texte qui a été conservée sous la forme de fragments. L'étude de l'origine de la Summa Alexandrinorum et des relations entre la Summa et les fragments et témoignages conservés dans d'autres langues et appartenant à autant de traditions parallèles et diverses vient compléter ce volume.